Design and VLSI implementation of high performance face recognition system - Dewan, Priyanka Das; Shamma, Tasnim Harun; Abbas, Afifa; Mondol, Raktim Kumar (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.